2017
DOI: 10.4269/ajtmh.17-0208
|View full text |Cite
|
Sign up to set email alerts
|

Water, Sanitation, and Hygiene in Rural Health-Care Facilities: A Cross-Sectional Study in Ethiopia, Kenya, Mozambique, Rwanda, Uganda, and Zambia

Abstract: Safe and sufficient water, sanitation, and hygiene (WaSH) prevent the spread of disease in health-care facilities (HCFs). Little research has been conducted on WaSH in HCF in sub-Saharan Africa. We carried out a cross-sectional study of WaSH in 1,318 randomly selected rural HCF (hospitals, health centers, health posts, and clinics) in regions throughout Ethiopia, Kenya, Mozambique, Rwanda, Uganda, and Zambia. Methods included questionnaires with head doctors and nurses to document WaSH access, continuity, qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 36 publications
10
59
2
3
Order By: Relevance
“…In this study, only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4). Similarly, Guo, Bowling (5) reported that less than 50% of rural HCFs in Uganda had access to improved water sources on premises, improved sanitation, and consistent access to water and soap for handwashing. Whereas Mulogo, Matte (4) and Guo,Bowling (5) give useful insights into WASH in HCFs in rural settings, their findings do not explicitly give a picture of the WASH status in a typically growing urban setting such as the Greater Kampala Metropolitan area (GKMA).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In this study, only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4). Similarly, Guo, Bowling (5) reported that less than 50% of rural HCFs in Uganda had access to improved water sources on premises, improved sanitation, and consistent access to water and soap for handwashing. Whereas Mulogo, Matte (4) and Guo,Bowling (5) give useful insights into WASH in HCFs in rural settings, their findings do not explicitly give a picture of the WASH status in a typically growing urban setting such as the Greater Kampala Metropolitan area (GKMA).…”
Section: Introductionmentioning
confidence: 59%
“…WASH in HCFs is fundamental for the provision of quality health care. Good WASH infrastructure and practices in HCFs, especially in maternity and primary care settings have the potential to reduce health care-related infections, increase trust and uptake of healthcare services, increase efficiency and improve staff morale (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In resource poor settings everywhere, there is limited capacity to provide care and save lives if infection rates escalate. Many public hospitals are in poor condition, and even basic hygiene may be lacking: working taps and sanitation are compromised; basins for handwashing lack soap (Guo et al 2017;Street 2014) and e.coli, staphylococcus, and other bacteria, frequently present on theater staff hands (Matuka et al 2018), contribute to nosocomial infection (Han et al 2019;Saleem et al 2019;Singh-Moodley et al 2018). In South Africa, beds are too close in ICU wards in both public and private hospitals to ensure isolation (Mahomed et al 2017).…”
Section: Reprioritizing Hospitals and Primary Care Clinicsmentioning
confidence: 99%
“…Provision of WASH services in HCFs is fundamental for the provision of quality health care. Good WASH services in HCFs, especially in maternity and primary care settings have the potential to reduce healthcare acquired infections (HAIs), increase trust and uptake of healthcare services, increase e ciency and improve staff morale (1,2). In addition, improved WASH supports the core universal health care aspects of quality, equity, and dignity for all people (1).…”
Section: Introductionmentioning
confidence: 99%
“…Mulogo,Matte (4) reported that only 38% of the HCFs had toilets with hand washing facilities; with only 24% having soap and water (4). Similarly, Guo, Bowling (5) reported that less than 50% of rural HCFs in Uganda had access to improved water sources on premises, improved sanitation, and consistent access to water and soap for handwashing. Whereas Mulogo, Matte (4) and Guo,Bowling (5) give useful insights into WASH in HCFs in rural settings, their ndings do not explicitly give a picture of availability of WASH services in a typically growing urban setting such as the Greater Kampala Metropolitan area (GKMA).…”
Section: Introductionmentioning
confidence: 99%